THE IMPLEMENTATION OF SEVEN EFFORTS OF LOCAL CHICKEN AT SAMBIRENTENG VILLAGE DISTRICT OF TEJAKULA BULELENG - I G., Sulastrawan; Inggriati, N. W. T.; Suarta, G. (Jurnal Peternakan Tropika; Vol 10 No 1 (2022): Vol. 10 No. 1 Tahun 2022; January - april, 2022)
The aims of this research is to find out: (1) the implementation of seven efforts of local chicken farming, (2) Factors related to the implementation of seven efforts of local chicken. This research was conducted in Sambirenteng Village, Tejakula, Buleleng Regency, which was conducted for three months, namely February 2021 to April 2021. The selection of research locations and the determination of respondents used the purposive sampling method. The total of respondents is determined by quota as many as 35 people, who are native local chicken  with a minimum ownership of 20 local chickens. Data analysis was conducted in a qualitative descriptive and the Spearman Correlation Stage Coefficient test (Siegel, 1997). The results of this study showing the  implementation of seven efforts of local chicken farming in Sambirenteng village is relatively moderate.The factors such as age, formal education, land ownership area, knowledge, and attitude have a real relationship (P<0,05). while for non-formal educational factors, and the skills have a very real relationship (P<0,01). The factors were not significantly related the experience of raising livestock, the number of livestock ownership, and motivation (P>0.10). Conclusion: the level implementation of seven efforts of local chicken farming in Sambirenteng village is classified as moderate, and factors related to:  age, formal education, non-formal education, land ownership area, knowledge, attitudes and skills. Suggestions that can be conveyed are that the government and native local chicken  in Sambirenteng Village can work together in increasing the implementation of seven effort of local chicken farming by conducting outreach activities with individual and group methods in order to increase the knowledge, attitudes and skills of farmers in implementing the seven effort of local chicken farming business. Key words :  counseling, knowledge, attitudes, skills